2008
DOI: 10.1634/stemcells.2007-1032
|View full text |Cite
|
Sign up to set email alerts
|

Mood Stabilizing Drugs Expand the Neural Stem Cell Pool in the Adult Brain Through Activation of Notch Signaling

Abstract: Neural stem cells (NSCs) have attracted considerable attention as a potential source of cells for therapeutic treatment of impaired areas of the central nervous system. However, efficient and clinically feasible strategies for expansion of the endogenous NSC pool are currently unavailable. In this study, we demonstrate that mood stabilizing drugs, which are used to treat patients with bipolar disorder, enhance the self-renewal capability of mouse NSCs in vitro and that this enhancement is achieved at therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…In Li-treated neurospheres, however, despite the induced increases in sizes, the survival of the neurospheres was not hampered but enhanced, implying that Li may enhance the oxygenation of the neurosphere ' s core to help the survival of neural progenitors. The increased number of viable NSCs by Li has also been shown by findings from other researchers, as a result of enhanced oxygenation and survival of neural progenitors ( Higashi et al, 2008 ;Zhou et al, 2011 ;Yin et al, 2014 ). Indeed, the enhanced survival was also seen in our model, as quantifying the apoptotic cells in Li-treated neurospheres showed a significant reduction compared to untreated neurospheres.…”
Section: Discussionsupporting
confidence: 64%
“…In Li-treated neurospheres, however, despite the induced increases in sizes, the survival of the neurospheres was not hampered but enhanced, implying that Li may enhance the oxygenation of the neurosphere ' s core to help the survival of neural progenitors. The increased number of viable NSCs by Li has also been shown by findings from other researchers, as a result of enhanced oxygenation and survival of neural progenitors ( Higashi et al, 2008 ;Zhou et al, 2011 ;Yin et al, 2014 ). Indeed, the enhanced survival was also seen in our model, as quantifying the apoptotic cells in Li-treated neurospheres showed a significant reduction compared to untreated neurospheres.…”
Section: Discussionsupporting
confidence: 64%
“…However at the doses used in the current study FLX has additional mechanisms of action, including a primary action of inhibiting serotonin reuptake (Wong et al, 1974). Increased activation of serotonin receptors results in cAMP-induced downstream effects, includingspecific activation of MAP kinases Erk1/2 (Tiraboschi et al, 2004), Notch signalling (Higashi et al, 2008) and BDNF release (Nibuya et al, 1995). Thus, FLX may increase BDNF through both ALLO-mediated and serotinergic mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…We found that ETH induced neurogenesis mainly due to increased NSC proliferation and neuronal differentiation. Several studies have previously suggested that multiple intricate cell signaling cascades, including PI3K⅐Akt (54 -57), Wnt⅐␤-catenin (58), and Notch (59), are involved in NSC proliferation, differentiation, and survival of (60). Herein, we demonstrated that ETH induces NSC proliferation and differentiation through recruitment of the PI3K/Akt/Wnt/␤-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Further, valproate has been shown to suppress the inhibitory effect of dexamethasone on the proliferation of adult DG-derived NPCs via the GSK-3␤ and ␤-catenin pathway (28). Mood-stabilizing drugs enhance the self-renewal capacity of mouse NSC in vitro and the NSC pool in the adult brain through the activation of Notch signaling (59). Similar to the action of various drugs reported in the above studies, we found that ETH also enhances NSC proliferation, neuronal differentiation, and survival in the hippocampal region.…”
Section: Discussionmentioning
confidence: 99%